JNK pathway plays a critical role for expansion of human colorectal cancer in the context of BRG1 suppression. Issue 10 (17th August 2022) - Yoshikawa, Takaaki; Fukuda, Akihisa; Omatsu, Mayuki; Namikawa, Mio; Sono, Makoto; Fukunaga, Yuichi; Masuda, Tomonori; Araki, Osamu; Nagao, Munemasa; Ogawa, Satoshi; Masuo, Kenji; Goto, Norihiro; et al.
Abstract: Tumor stem cells (TSCs), capable of self‐renewal and continuous production of progeny cells, could be potential therapeutic targets. We have recently reported that chromatin remodeling regulator Brg1 is required for maintenance of murine intestinal TSCs and stemness feature of human colorectal cancer (CRC) cells by inhibiting apoptosis. However, it is still unclear how BRG1 suppression changes the underlying intracellular mechanisms of human CRC cells. We found that Brg1 suppression resulted in upregulation of the JNK signaling pathway in human CRC cells and murine intestinal TSCs. Simultaneous suppression of BRG1 and the JNK pathway, either by pharmacological inhibition or silencing of c‐JUN, resulted in even stronger inhibition of the expansion of human CRC cells compared to Brg1 suppression alone. Consistently, high c‐JUN expression correlated with worse prognosis for survival in human CRC patients with low BRG1 expression. Therefore, the JNK pathway plays a critical role for expansion and stemness of human CRC cells in the context of BRG1 suppression, and thus a combined blockade of BRG1 and the JNK pathway could be a novel therapeutic approach against human CRC. Abstract : It is reported that BRG1 suppression causes regression of human colorectal cancer cells. Moreover, simultaneous suppression of BRG1 and the JNK pathway resulted in even stronger inhibition of the expansion of human CRC cells compared to Brg1 suppression alone. Therefore, combined blockade of BRG1 and the JNK pathway could be a novel therapeutic approach against human CRC.